(untitled) (Oshada, 2025)
Low levels of physical activity have encouraged the widespread use of numerical targets, such as 10,000 steps per day, as public health promotion tools. Despite their popularity, the effectiveness of step-based targets depends not only on campaign exposure but also on how individuals perceive the scientific evidence underlying these recommendations. This study examines the effect of evidence-based perception of the 10,000-step target on physical activity intention using a Structural Equation Modeling–Partial Least Squares (SEM–PLS) approach. A quantitative explanatory cross-sectional survey design was employed, with data collected at a single point in time through a questionnaire from 220 adults exposed to step-based physical activity programs or information. Evidence-based perception was modeled as a latent construct reflecting scientific understanding, perceived validity, and rationality of the step target, while physical activity intention was measured through indicators of readiness and behavioral commitment. The results indicate that evidence-based perception has a positive and significant effect on physical activity intention, with a strong path coefficient and a moderate R-square value. These findings suggest that evidence-based understanding plays a critical role in shaping physical activity intention, beyond the normative function of step targets. The study concludes that step-based physical activity promotion will be more effective when accompanied by evidence-based communication that fosters rational and informed acceptance of health recommendations.